How balanced are you? Bilingualism and the development of attentional control in English-Mandarin preschool children - Chan, Clara Gek Hoon (2018)
In recent years, research interest on bilingualism and its relation to cognitive control has grown. Given that engaging in the cognitive processes of language management in the brain is likely to result in changes to the neural system to improve cognitive efficiency, bilingualism is expected to positively benefit cognitive control. However, the experience of bilingualism is varied. Some individuals are more comparable in their proficiency in both languages (more-balanced), while others are much more proficient in their dominant language than they are in their weaker language (less-balanced). The Adaptive Control hypothesis (Green & Abutalebi, 2013) is a theoretical framework proposed as to how bilinguals manage two languages in their minds. As part of the theory, they highlight the importance of context; three different bilingual conversational contexts were identified, and differing cognitive demands were attributed to those three contexts. The main research question in the current thesis is to examine the relation between bilingualism balance and attentional control in preschool children. Young children have high levels of attentional plasticity; to examine the relation in this age group has far reaching implications both theoretically and practically. Previous studies have found a positive relationship between bilingualism balance and attentional control, with more-balanced bilinguals performing better on the attention task than the less-balanced bilinguals (e.g. Carlson & Meltzoff, 2008; Poarch & van Hell, 2012). However, there have been some research gaps. Firstly, due to the complex nature of measuring language proficiency and experience, there is yet to be a commonly accepted measure of bilingualism balance. Secondly, results comparing bilingualism balance and attention have not been consistent across studies; there is a lack of information regarding which aspect of the bilingualism experience is related to which subcomponent of attention. Thirdly, there is also a lack of understanding of the mechanism underlying how bilingualism balance relates to attentional control. We propose a contextual-based attention control perspective as an underlying mechanism, by highlighting the importance of different language contexts and the role of attention in language monitoring and selection. We contend that, due to the differences in the contexts that a more-balanced bilingual experiences as compared to a less-balanced bilingual, the cognitive demands differ between them and therefore the more-balanced bilingual will have higher cognitive control than the less-balanced bilingual. In response to the research gaps, we conducted three studies. In Study 1, we set out to determine the real-world bilingual experience correspondence of our chosen index of bilingualism balance: vocabulary tests ratios. We compared parental reported exposure and use of each language with receptive and expressive vocabulary scores. Results showed moderately strong correlations between parental reported scores and the vocabulary tests ratios, supporting the use of this balance index in the subsequent studies. In Study 2, we examined the relation between bilingualism balance and attentional control. Using the ratio of receptive vocabulary across languages as a proxy for language exposure, and expressive vocabulary ratio as a proxy for language production, we compared the vocabulary ratios to different network performances on the Attention Network Test (ANT). Results indicated that in general, more-balanced bilinguals (higher ratio) performed better on the ANT as compared to the less-balanced ones. Specifically, both aspects of language experience (exposure and production) were related to two of the attentional networks (alerting and conflict). Study 3 was designed to endeavor to understand the mechanism behind how bilingualism balance affects attentional control. To investigate the importance of different linguistic contexts, the aspect we proposed to be what more and less-balanced bilinguals differ on, we experimentally induced different language contexts to see the subsequent performance on the ANT. Participants were randomly assigned them to one of three conditions: before completing the ANT, they had to complete a picture-recognition task either (1) in their dominant language, (2) in their weaker language, or (3) in a mixture of the two languages (to simulate language-switching). It was found that the children who completed the language task in their weaker language and the language switching condition showed higher overall accuracy in the subsequent ANT compared to those who completed the task in their dominant language. Taken together, the studies suggest that more-balanced bilingual children (as compared to less-balanced ones) exhibit better attentional control, and this difference may be due to the differences in exposure to their languages between these two groups; the less-balanced bilinguals are exposed mostly to their dominant language, and since that context does not require as much cognitive demands, they are less likely to practice attentional control, as compared to being in a highly bilingual environment, which is more common in more-balanced bilinguals. Given the cultural and societal differences inherent in bilingualism all over the world, caution needs to be taken when generalizing the conclusions, but the results have both theoretical and practical implications on promoting balanced bilingualism among young bilinguals to benefit their attentional control.